Improving Scientific Creativity and Scientific Attitude of Students through Creative Responsibility Based Learning on Energy-Work Materials during the Covid-19 Pandemic - Khairunnisa Maharani; Saiyidah Mahtari; Suyidno Suyidno (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
Scientific creativity and scientific attitude play an important role in learning physics, but both of those competencies are not properly trained. Therefore, the purpose of this study is to describe the effectiveness in increasing scientific creativity and students’ scientific attitude. The research is part of a development research using the ADDIE model. In the ADD (Analysis, Design, Development) stage, a CRBL package has been produced that has met the valid and reliable criteria; so that the device can be continued at the IE (Implementation, Evaluation) stage by using a one group pre-test and post-test design. The research subjects were 22 students of class X in one of the senior high schools in the city of Banjarmasin. The data were obtained using instruments of scientific creativity test and scientific attitude questionnaires. The results of the study show that the n-gain of scientific creativity is 0.34 in the medium criteria, although every scientific creativity indicator has not reached the school minimum completeness criteria due to the online learning process. Also, the students’ scientific attitude has increased at each meeting in good criteria. Thus, CRBL is effective in increasing scientific creativity and students’ scientific attitudes during the COVID-19 pandemic.